A UNIQUE COMBINATION OF AYURVEDIC MEDICINES AND PANCHAKARMA IN MANAGEMENT OF DARUNAKA: A SINGLE CASE STUDY - Pranjal Sanjay Jain; Amey Chandrakant Nakil; Vivek Shrirampant Chandurkar (AYUSHDHARA, 2021)
In today’s era, Darunaka (Dandruff) is one of the irritative and embarrassing diseases which have high prevalence rate. The disease is mainly concerned with hair root. Due to the poor cleaning, pollution, changing lifestyle and food habits that ultimately leads to the disease. According to Ayurveda, it can be correlated with Seborrhoic dermatitis. Cardinal symptoms of Darunaka are Kandu (itching), Rukshata (dryness), Twaksphuthan (cracking of skin), Keshachutti (falling of hair). As dandruff doesn’t produce any hazards effect to body but cosmetically it looks ugly. It is mainly due to the vitiation of Vata and Kapha Dosha. In present paper, a 30yr male patient came to the OPD with symptoms of Shweatvarniya Twakvevarnya at Shir Pradesh, Kandu, Twaksphuthan, Keshachyuti, Rukshata, since 3yrs along with he also developed Kurpar and Vankashanpradeshi Twakavaivarnya and Kandu. He was treated with the help of Ayurvedic medicines and some Panchakarma procedures. The improvement provided by therapy was assessed on the basis of sign and symptoms before and after treatment.